Physiotherapy management of post-operative ACL rehabilitation: a cross-sectional survey in Gauteng, South Africa - Robbertse, Colett (My University, 2024)
Background: There are a variety of protocols used by physiotherapists for postoperative ACL rehabilitation. The study aimed to determine the management strategy and treatment modalities currently used by physiotherapists in post-operative ACL rehabilitation, in Gauteng, South Africa. Method: The methodology of the study was a quantitative cross-sectional study. A selfdesigned questionnaire was developed for this study. The questionnaire comprised of three sections: Part 1 which captured the demographic information, part 2 which captured specific questions regarding rehabilitation protocol and part 3 which captured questions about physiotherapy goals and outcome measures. The questionnaire was loaded on the REDcap online survey system. The link with introduction, explanation, ethical approval and consent to participate was sent to the SASP and PASA for distribution to their members. Due to a poor response rate from the participants, the questionnaire was then distributed via social media. The data collection term was from 15 December 2021 up to 27 May 2022. Results: 120 participants accessed the questionnaire. Only 46.6% of the responses captured could be used for data analysis. The exclusions included 22 incomplete responses and 42 responses from participants not working in Gauteng. The analysis of the survey revealed that there is a great variety of protocols, physiotherapy modalities, exercise prescription and outcome measured used in post-operative ACL rehabilitation by physiotherapists in Gauteng, South Africa. Conclusion: More research about evidence-based protocols, physiotherapy modalities and exercise prescription are required to improve the outcomes of postoperative ACL rehabilitation.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Physiotherapists; Treatment modalities; Management strategy